2014
DOI: 10.1111/joss.12081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Nonvolatile Fraction on the Sensory Perception of 40% (v/v) Ethanol‐Containing French Grape Brandies

Abstract: Several studies performed on wines have shown that nonvolatile and matrix components can have an impact on sensory perception through physicochemical and/or sensory interactions. In distilled spirits and as for many other food products, relationships between these components and the sensory perception are still misunderstood. In the present study, we investigated the impact of nonvolatile components on the sensory perception of two 40% (v/v) ethanol-containing French grape brandies with different compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This result was consistent with the ones obtained in a previous study, in which we had shown that brandy components responsible for taste and trigeminal sensations had only a low impact on perception differences among brandies with different aging. [3] Sensory profile results were useful to characterize global perceived intensities differences between brandies with different aging, but no temporal information could be obtained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result was consistent with the ones obtained in a previous study, in which we had shown that brandy components responsible for taste and trigeminal sensations had only a low impact on perception differences among brandies with different aging. [3] Sensory profile results were useful to characterize global perceived intensities differences between brandies with different aging, but no temporal information could be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This observation could be related to the presence of higher amounts of alcohols in intermediary and old brandies than in the younger brandy (Table 3). [3] The aromatic persistence was the longest after the consumption of brandies C to E, which still occurred at the standardized time of 70-75%, especially for woody perception. Results from TDS were in accordance with those of the sensory profile but provided additional quantitative information about the temporal aspect of aromatic perception, notably after the product was spat out.…”
Section: Tds Curves: Changes In Perception Over Brandy Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative difference in the composition of these two fermented foods is at the basis of the difference in the aromatic notes between "bikedi" and "nsamba". The characterization of these volatile compounds is an important piece of information for understanding the perception of odours, flavor and aromas (Shittu and Adedokun, 2010;Biasioli et al, 2011;Fiches et al, 2013).…”
Section: Resultsmentioning
confidence: 99%